Ilustrasi Interaktif Pengenalan dan Pengolahan Sampah Sebagai Media Edukasi - Arista Cahyani; Amalia Hartiningrum; Sonhaji Arif; Putra Uji Deva Satrio; Akhya' Muhammad Khaidzir (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2025)
The mismanagement of waste can have severe impacts on the environment and public health. According to data from the Ministry of Environment and Forestry (KLHK), public awareness in Indonesia regarding waste segregation remains low, emphasizing the need for education on waste management, especially for younger generations. This design aims to create an interactive illustration book as an engaging and effective educational tool to introduce children aged 10-12 to waste types and the 3R principles (Reduce, Reuse, Recycle). The method employed is Research and Development (R&D) using the 4D model, which includes Define, Design, Develop, and Disseminate stages. The interactive illustration book is designed with an appealing cartoon illustration style, complemented by interactive elements such as mazes, matching games, lift-a-flap features, and a quiz on the last page. Data were collected through observation, interviews, and literature studies. The results of the design indicate that the interactive illustration book effectively enhances children's understanding of waste types and their management.